Unlocking therapeutic potential: dual gene therapy for ameliorating the disease phenotypes in a mouse model of RPE65 Leber congenital amaurosis - Liu, Yanbo; Tai, Jingjie; Yu, Chaofeng; Xu, Dan; Xiao, Dan; Pang, Jijing (Frontiers in Medicine, 2024)
Leber congenital amaurosis (LCA) is the most common genetic cause of congenital visual impairment in infants and children. Patients with LCA who harbor RPE65 mutations exhibit a deficiency in photoreceptor rhodopsin, leading to severe night blindness and visual impairment following birth.Since either gene replacement therapy or anti-apoptosis therapy alone cannot maintain both functional and morphological normality for a long time in the animal model, we propose a robust treatment strategy, that is, gene replacement therapy combined with anti-apoptotic therapy to protect photoreceptors from further degeneration while compensating for lost RPE65 function. Here, rd12 mice were injected subretinally at postnatal day 14 with four vector administrations respectively. At 6 months after treatment, it was discovered that injection of three vectors, AAV8 (Y733F)-CBA-hRPE65, AAV8(Y733F)-CBA-hRPE65-BCL-2-L10 and mixture of half-dose AAV8(Y733F)-CBA-hRPE65 2 This is a provisional file, not the final typeset article and half-dose AAV8 (Y733F)-CBA-BCL-2-L10, could partially restore the visual function of rd12 mice. Meanwhile, these treated eyes also exhibited a thicker outer nuclear layer (ONL) structure.However, despite the fact that the eyes of rd12 mice injected with the AAV8 (Y733F)-CBA-BCL-2-L10 vector displayed a slightly thicker ONL structure compared to untreated eyes, the visual function of the treated eyes did not recover. Continuing the observation period to 12 months after treatment, we found that compared to rd12 mice at 6-month post-treatment, rd12 mice injected with AAV8 (Y733F)-CBA-hRPE65 or mixture of half-dose AAV8(Y733F)-CBA-hRPE65 and half-dose AAV8 (Y733F)-CBA-BCL-2-L10 exhibited varying degrees of decline in both visual function and ONL thickness.However, in the case of rd12 mice injected with the AAV8(Y733F)-CBA-hRPE65-BCL-2-L10 vector, the ONL thickness remains consistent at both 6 and 12 months after treatment. These mice continued to maintain a relatively strong visual function and showed restoration in the levels of RPE65 and Rhodopsin protein expression. Our findings illustrate that early postnatal treatment with AAV vectors containing both the hRPE65 gene and the Bcl-2L10 anti-apoptotic gene provide enhanced and sustained retinal protection.